RUFY4 exists as two translationally regulated isoforms, that localize to the mitochondrion in activated macrophages - Valečka, Jan (R Soc Open Sci, 2021)
We report here that RUFY4, a newly characterized member of the ‘RUN and FYVE domain-containing’ family of proteins previously associated with autophagy enhancement, is highly expressed in alveolar macrophages (AM). We show that RUFY4 interacts with mitochondria upon stimulation by microbial-associated molecular patterns of AM and dendritic cells. RUFY4 interaction with mitochondria and other organelles is dependent on a previously uncharacterized OmpH domain located immediately upstream of its C-terminal FYVE domain. Further, we demonstrate that rufy4 messenger RNA can be translated from an alternative translation initiation codon, giving rise to a N-terminally truncated form of the molecule lacking most of its RUN domain and with enhanced potential for its interaction with mitochondria. Our observations point towards a role of RUFY4 in selective mitochondria clearance in activated phagocytes.